2022
DOI: 10.3389/fmed.2022.880909
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Serum Soluble Tim-3 Level Is Related to the Progression of Diseases After Hepatitis Virus Infection

Abstract: BackgroundViral hepatitis is a widespread and serious infectious disease, and most patients with liver cirrhosis and hepatocellular carcinoma are prone to viral infections. T cell immunoglobulin-and mucin-domain-containing molecule-3 (Tim-3) is an immune checkpoint molecule that negatively regulates T cell responses, playing an extremely important role in controlling infectious diseases. However, reports about the role of serum soluble Tim-3 (sTim-3) in hepatitis virus infection are limited. Therefore, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This finding is consistent with a study by Chen et al (2022), which reported significantly higher concentrations of TIM-3 protein in the serum of patients with viral hepatitis compared to healthy controls. The study also emphasized the association of TIM-3 protein with the extent of liver damage and its potential influence on the pathogenesis of the disease [35]. Similarly, in chronic viral infections such as HIV and HBV, increased TIM-3 expression correlated with disease progression and viral load, while decreased frequencies of TIM-3 positive T-cells correlated with antiviral treatment and resolution of viral infection [36,37], suggesting that TIM-3 expression levels may be a prognostic indicator of disease progression in chronic viral infections [38].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a study by Chen et al (2022), which reported significantly higher concentrations of TIM-3 protein in the serum of patients with viral hepatitis compared to healthy controls. The study also emphasized the association of TIM-3 protein with the extent of liver damage and its potential influence on the pathogenesis of the disease [35]. Similarly, in chronic viral infections such as HIV and HBV, increased TIM-3 expression correlated with disease progression and viral load, while decreased frequencies of TIM-3 positive T-cells correlated with antiviral treatment and resolution of viral infection [36,37], suggesting that TIM-3 expression levels may be a prognostic indicator of disease progression in chronic viral infections [38].…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous description, sTim-3 may serve as a biomarker for patients with osteosarcoma [ 45 ] and graft-versus-host disease [ 46 ]. Increased serum sTim-3 was related to the progression of hepatitis virus infection diseases [ 47 ], which indicated that Tim-3 can act as a biomarker beside as a clinical target. On this basis, Tim-3 was considered to be closely associated with the clinical prognosis of chronic HBV infection [ 48 ], which could be used as a new index to evaluate the prognosis in CHB patients.…”
Section: Discussionmentioning
confidence: 99%
“…As Gal-9 circulates in the serum in a soluble form, soluble TIM-3 (sTIM-3) can also be found in the circulation, but its role in the disease is not yet clarified. In CHB patients, sTIM-3 levels are increased in the serum compared to healthy controls, and are associated with a higher viral burden and liver inflammation ( 170 , 172 , 173 ). Moreover, when looking at different stages of the disease from inactive hepatitis to liver cirrhosis and cancer, sTIM-3 levels rise gradually suggesting a close association with the disease progression ( 172 , 173 ).…”
Section: Dynamic and Disturbances Of Immune Checkpoints In T Cells An...mentioning
confidence: 99%
“…In CHB patients, sTIM-3 levels are increased in the serum compared to healthy controls, and are associated with a higher viral burden and liver inflammation ( 170 , 172 , 173 ). Moreover, when looking at different stages of the disease from inactive hepatitis to liver cirrhosis and cancer, sTIM-3 levels rise gradually suggesting a close association with the disease progression ( 172 , 173 ). However, antiviral treatment did not modulate sTIM-3 levels in treated patients which were rather more elevated in the NUC-treated group compared to the non-treated one ( 170 ).…”
Section: Dynamic and Disturbances Of Immune Checkpoints In T Cells An...mentioning
confidence: 99%